PENTINGNYA KEPEMIMPINAN DALAM MANAJEMEN PENDIDIKAN - Loso Judijanto; Amândio de Araújo Sarmento; Saefrudin Saefrudin; Andro Ruben Runtu; M. Hamdy Meydiansyah (FAKULTAS TARBIYAH INSTITUT AGAMA ISLAM SULTAN MUHAMMAD SYAFIUDDIN SAMBAS, 2024)
Leadership in education management has a crucial role in determining the success of educational institutions. Effective leadership is able to provide clear direction, inspire and motivate all members of the educational community to achieve a common vision and goals. Strong educational leaders will create a positive school culture through open communication, co-operation and active participation, which contributes to a productive learning environment. In addition, leadership in education management also demands the ability to integrate vision into action, through efficient resource management, appropriate staff development programmes and continuous evaluation. Thus, the success of educational institutions depends largely on the balance between visionary leadership and structured management.